Price relationships between bond markets - BLAGUN, Ivan (Scientific journal «World of Finance», 2019)
Introduction. The strengthening of globalization processes leads to a greater integration of the domestic financial market into the global financial market, especially bond market. Ukraine is under significant influence of world economic processes. In this context the impact that has on the state of the domestic market of Ukraine our financial market, as well as the actions of American financial regulators. On the background of the formation of excessive debt structure of the global financial market, including the US market, the financial market of Ukraine in recent time, there is also the nature of the debt market which is a key financial instrument is bonds, i.e. government bonds. Not less important and of the dual influence of the two basic segments of the financial market between market shares and bonds that affects the efficiencyof capital investors.The purposeis the research of the relationships that are formed between the markets of shares and bonds on the example of financial markets of the USA and Ukraine.Results. The price relationship between the bond markets of countries with different levels of development has been considered. For the basic indicators, characterizing the main parameters of the bond market the analysis of the influence of the US bond market to the domestic market, determined correlations between the rates of return on ten-year bonds. It has been established that the time series of the rate on ten-year bonds have signs of nonstationarity. Based on the identified nonstationarity time series were analyzed for cointegration. It is determined that the modeling-level rate bonds in Ukraine can be improved by applying advanced Sapsan the value of the rate of the bonds in the United States.Conclusions. The results do not indicate the manifestation of a dependence between the value of the rates of ten-year bonds in the United States and Ukraine. Also there is no dependence between the current growth rate of bonds. A more detailed analysis also showed the absence of long-term balance between the rates of these bonds. The analysis of the interaction between equity markets and bond between them showed that the existing dual influence should be viewed through the prism of external factors that can lead to very different behavior of these markets, on the one hand they are competitors, in terms of raising capital, on the other in some periods, they are characterized by complementarity.